Water management challenges in construction projects: A look at Costa Rica - Cruz-Zúñiga, Nidia (2025)
Water is a very valuable resource and is becoming increasingly scarce in the world. There is great pressure to provide the general population with the water required for all its activities, and in the construction sector in particular the demand is high and inflexible. This article presents a summary of some research carried out with undergraduate students regarding the panorama of water consumption and management in civil engineering construction projects in the country. The results presented do not correspond to a statistical sample, but they allow us to reflect some of the main challenges that the sector faces. The results have shown how water use patterns do not meet sustainability criteria in most of the cases analyzed, and in particular consumption seems to have a linear behavior that responds more to the duration of the work than to the real needs of the resource. It is evident that, although there is awareness of the importance of saving water, it is not a priority to implement concrete measures to achieve it. The perception of professionals and technicians who work in construction seems to indicate that the issue is relevant, but they themselves show a lack of awareness and an inertia that is difficult to change in the work. It is concluded that if the construction sector wants to promote sustainable practices for water resources, hard work is required to change the culture, customs and consumption habits from different angles and different stakeholders.